Determination of lipase inhibitory compound from aquilaria subintegra matured leaves extract via pretreatment using bath sonicator: effect of sonication temperature / Amanina Abdul Manan - Abdul Manan, Amanina (2017)
Obesity is recognized as the most widespread metabolic disease. This disease was believed to be treated by reducing fat absorption through the inhibition of pancreatic lipase. The natural resources as polyphenol compound such as phenolic and flavonoid can be used as pancreatic lipase inhibitor. Pancreatic lipase is a key enzyme in dietary triacylglycerol absorption, hydrolysing triacylglycerol to monoacylglycerol and fatty acid. Those compound can be found in Aquilaria subintegra, a type of leaf of Gaharu. This study was conducted in two different types of parameter where the leaves were ground to 0.25 mm, 0.5 mm and 1.0 mm and pre-treated by ultrasonification with temperature of 40°C, 50°C, 60°C, 70°C and 80°C. The presence of phenolic and flavonoid compound in A. subintegra leaves extract was analyzed by using Masterizer Malvern 2000E and High performance liquid Chromatography (HPLC) to validate the presence of phenolic and flavonoid compound. From the analysis, the best temperature of ultrasonification is 60°C and the sample size 0.25 mm has the largest concentration both in flavonoid and phenolic.